Mucins: the frontline defence of the lung - Ridley, Caroline; Thornton, David J (Biochemical Society transactions, 2018)
Mucus plays a vital role in protecting the lungs from environmental factors, but conversely, in muco-obstructive airway disease, mucus becomes pathologic. In its protective role, mucus entraps microbes and particles removing them from the lungs via the co-ordinated beating of motile cilia. This mechanism of lung defence is reliant upon a flowing mucus gel, and the major macromolecular components that determine the rheological properties of mucus are the polymeric mucins, MUC5AC and MUC5B. These large O-linked glycoproteins have direct roles in maintaining lung homeostasis. MUC5B is essential for interaction with the ciliary clearance system and MUC5AC is up-regulated in response to allergic inflammatory challenge. Mucus with abnormal biophysical properties is a feature of muco-obstructive respiratory disease and can result from many different mechanisms including alterations in mucin polymer assembly, mucin concentration and the macromolecular form in mucus, as well as changes in airway surface hydration, pH and ion composition. The abnormal mucus results in defective lung protection via compromised ciliary clearance, leading to infection and inflammation.